An Overview of Online Loan (Pinjol) Usage Among Medical Students of Universitas YARSI, Cohorts 2023–2024, and Its Review from an Islamic Perspective - Dayang Serly Safitri; Ferryal Basbeth; Aryenti Aryenti; Muhammad Fazlurrahman Anshar (International Journal of Health Engineering and Technology, 2026)
The increasing accessibility of online loan (pinjol) services has influenced financial behavior among students, potentially leading to consumptive habits and financial risks. Among medical students with demanding academic responsibilities, the use of online loans may impact financial stability and decision-making. From an Islamic perspective, financial transactions must comply with Sharia principles, avoiding elements such as riba (usury), gharar (uncertainty), maysir (gambling), and zhulm (injustice). This study aims to analyze the overview of online loan usage among Medical Students of Universitas YARSI Cohorts 2023–2024 and examine it from an Islamic perspective. This study used a quantitative survey design with a total sampling technique involving active medical students of Universitas YARSI Cohorts 2023–2024 who met the inclusion criteria. Data were collected through an anonymous online questionnaire distributed via Google Forms using Likert-scale (1–5) questions. The variables measured included economic factors, social factors, consumptive behavior, ease of access, and financial impact. The instrument was tested for validity and reliability prior to data collection. The findings indicate that the main factors influencing online loan usage among students are ease of access and consumptive lifestyle, both showing significant relationships with usage behavior. Economic and social factors were not significantly associated. Online loan usage is linked to higher consumptive behavior and has implications for students’ financial conditions, including potential financial burden. Students generally perceive online loans as a practical and quick financial solution. Some respondents exhibit repeated usage patterns, indicating a risk of dependency. Awareness of the risks and intention to reduce usage were observed among a portion of students. Differences were also found in understanding online loans as riba, with non-users demonstrating better awareness. Online loan usage among YARSI medical students is primarily driven by convenience and consumptive behavior, with notable impacts on financial management. From an Islamic perspective, online loans are permissible only if they adhere to Sharia principles. However, most conventional online lending practices involve elements of riba and are therefore not permissible, highlighting the need for greater financial literacy and caution among students.